The Effectiveness of IoT-Based Flipped Classroom Model on Students' Critical Thinking Skills: A Meta-Analysis - Syafruddin Syafruddin; Ika Agustina; Jemmy Jemmy; Komari Komari; Tomi Apra Santosa (Postgraduate, University of Mataram, 2023)
The research objective is to determine the effectiveness of the Internet of Things (IoT)-based Flipped Classroom model on students' critical thinking skills. This type of research is meta-analysis research. Data sources come from national and international journals. The inclusion criteria in this research are that research must come from journals and proceedings indexed by SINTA, WOS and Scopus; Research from journals published from 2019-2023; Research must use experimental or quasi-experimental methods; Data source searches must be from the G,oogle Scholar, Taylor & Francis, ScienceDirect, IEEE, and ERIC databases; and Research reports values (t), (r) and (f) and sample size > 20 students. Data analysis with the help of the JSAP application. The results of this study conclude that the summary effect size or mean effect size (rRE = 0.764; p < 0.001) has a high influence. In this meta-analysis, the author, year of publication, country of research, values (r), (t), and (f) are analyzed. These findings show that the Internet of Things (IoT) based flipped classroom model is effective in improving students' critical thinking skills